Speed control of battery and super-capacitor powered EV/HEV using PID and fuzzy logic controller. (3rd June 2022) - Tiwari, Nitesh; Yadav, Shekhar; Arya, Sabha Raj
This paper's objective is to obtain the fine speed control of EV/HEV and analysed the behaviour of the PID controller and FLC. FLC-based drive scheme is more suited for achieving the fine speed control compared to the traditional PID controlled drive scheme. FLC-based EV motor drives perform well during normal and abnormal working conditions including environmental parameter variation and high resistance fault condition compared to PID controller-based EV motor drive scheme. The battery bank is utilised as a power source for the conventional EV but this paper proposed the combination of the battery bank (followed by the UBBC) and super-capacitor bank (followed by the BBBC) as a power source for HEV. A super-capacitor provides power at the time of sudden or peak demand and extracts power at the time of regenerative breaking. All the results are verified with the help of simulation software named as MATLAB and Simulink.